2012
DOI: 10.5688/ajpe76592
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Patients in Pharmacy Education

Abstract: A review of the literature relating to the use of virtual patients in teaching pharmaceutical care to pharmacy students was conducted. Only 7 articles met the inclusion criteria for the review and 4 of the studies were conducted in North America. Few articles identified by the review used virtual patient technology that was true-to-life and/or validated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 32 publications
0
31
0
1
Order By: Relevance
“…As active learning techniques have been encouraged in pharmacy education, an increase in the use of technology has often followed [ 47 ]. The virtual patient technique is especially useful for training students for pharmaceutical care practice because it enables the application in clinical practice of the theoretical knowledge acquired by the students during their studies [ 49 ]. A further relevant issue is the application of knowledge in pharmacy practice.…”
Section: Discussionmentioning
confidence: 99%
“…As active learning techniques have been encouraged in pharmacy education, an increase in the use of technology has often followed [ 47 ]. The virtual patient technique is especially useful for training students for pharmaceutical care practice because it enables the application in clinical practice of the theoretical knowledge acquired by the students during their studies [ 49 ]. A further relevant issue is the application of knowledge in pharmacy practice.…”
Section: Discussionmentioning
confidence: 99%
“…There are many VP applications, designs and definitions, which can incorporate modalities such as voice recognition, animations and videos. VP variations are recognised to be problematic when comparing studies2–4 and so the following definition was adopted.…”
Section: Introductionmentioning
confidence: 99%
“…A narrative review by Jabbur-Lopes et al highlighted that there were only seven studies on pharmacy VPs 2. Although the review covered a broad range of technology it only included undergraduate students and did not consider differences between the technologies or their purposes but focused on the users’ experiences 2. The review concluded that VPs have ‘the potential to be an innovative and effective educational tool in pharmacy education’ .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent review by Jabbur-Lopes and colleagues focused on the use of VH in pharmaceutical care education to pharmacy students (Jabbur-Lopes et al, 2012). Using less stringent criteria than the work of Cook et al, this review found seven articles, four of which were conducted in North America.…”
Section: State Of the Artmentioning
confidence: 99%